2007
DOI: 10.1109/edoc.2007.4383994
|View full text |Cite
|
Sign up to set email alerts
|

Validating Adequacy and Suitability of Business-IT Alignment Criteria in an Inter-Enterprise Maturity Model 202

Abstract: Aligning requirements of a business with its information technology is currently a major issue in enterprise computing. Existing literature indicates important criteria to judge the level of alignment between business and IT within a single enterprise. However, identifying such criteria in an inter-enterprise setting-or rethinking the existing onesis hardly addressed at all. Business-IT alignment in such settings poses new challenges, as in inter-enterprise collaborations, alignment is driven by economic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…However, that research has also found some similarities between the two sectors. Moreover, we have also found evidence, in the case studies we have conducted to design the ICoNOs MM (Santana Tapia et al, 2007;Santana Tapia et al, 2008a;Santana Tapia et al, 2008b), which confirms some similarities. We do believe that CNOs in both sectors begin a BITa project with a solid mission statement that drives the processes to meet the shared goals.…”
Section: Validity Threatssupporting
confidence: 62%
“…However, that research has also found some similarities between the two sectors. Moreover, we have also found evidence, in the case studies we have conducted to design the ICoNOs MM (Santana Tapia et al, 2007;Santana Tapia et al, 2008a;Santana Tapia et al, 2008b), which confirms some similarities. We do believe that CNOs in both sectors begin a BITa project with a solid mission statement that drives the processes to meet the shared goals.…”
Section: Validity Threatssupporting
confidence: 62%
“…On the other hand, it has been argued that software cities should not be "designed" in the traditional way, but rather "planned" and "regulated" similarly to urban planning. Business-IT alignment is also an active research area, but only a few works [25,26] study its extension with a focus on inter-enterprise and complex environments. However, they do not provide general conclusions.…”
Section: Related Workmentioning
confidence: 99%
“…5) Research of ultra-large-scale systems is important for next-generation enterprise computing. We find some of the software engineering and enterprise computing techniques [9,20,26] invaluable in creating reference architectures. However, others are not designed with the industry-wide scale in mind.…”
Section: ) Systematic Evaluation Of Rule-based Architectures Requirementioning
confidence: 99%
“…Our previous work [273] helped us to develop such codification based on the domains included in our ICoNOs MM, i.e., partnering structure, IS architecture, process architecture, coordination and cost management. This codification was later used in the analysis of the interviews transcripts.…”
Section: Research Design and Findingsmentioning
confidence: 99%
“…The final B-ITa domains are presented in Chapter 6 after using three other case studies for generalization of findings. A preliminary version of this chapter has been published in the proceedings of the 11th IEEE International EDOC Enterprise Computing Conference [273].…”
Section: Introductionmentioning
confidence: 99%